Penyusunan Laporan keuangan berdasarkan ISAK 35 Pada Kelompok Tani Mekar Sari - Oktavia, Yola (Jurnal Akuntansi Syariah (JAkSya), 2021)
Farmer groups obtain resources to carry out these activities from grants, assistance or donations and the purpose of its establishment is to have the same interests and to prosper its members. Easy-to-understand financial reporting is carried out in accordance with generally accepted accounting standards. The standards governing the financial reporting of non-profit entities are the interpretation of financial accounting standards no. 35. So the purpose of this study is to find out how the preparation of financial statements that should be in the Mekar Sari farmer group based on ISAK 35. The data collection technique that the author uses is through documentation and direct interviews, the financial statements made by the Mekar Sari farmer group are not in accordance with regulations ISAK 35 because the reports made are only limited to monthly reports or cash in and out reports. While the reports that will be generated from this research are the statement of financial position, comprehensive income report, report on changes in net assets, cash flow statement and notes to financial statements.